(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Smash is one of the most decisive and powerful techniques in badminton, requiring a combination of strength, speed, and precision to successfully score points. Among the physical attributes essential for an effective smash, arm muscle strength plays a critical role, particularly in generating explosive force during overhead strokes. This study aims to examine the effect of tricep dip training on the smash ability of badminton athletes aged 13–16 years at PB Daun Muda Banjarbaru. Utilising a quasi-experimental method with a pretest-posttest control group design, 20 athletes were divided into two groups: an experimental group that received a six-week tricep dip training intervention and a control group that followed their regular training regimen without specific arm strength exercises. Pre- and post-tests were conducted to assess improvements in smash ability, and data were analysed using the Paired Sample T-Test in SPSS version 23. The analysis revealed a statistically significant improvement in the experimental group’s smash performance, with a p-value of 0.000 (<0.05), indicating the effectiveness of the tricep dip intervention. No significant improvement was observed in the control group. These findings suggest that targeted arm muscle strength training, particularly tricep dips, can significantly enhance the performance of smash shots in young badminton players. The results also highlight the importance of incorporating structured strength training programs into youth athlete development models to optimise skill acquisition and performance outcomes.